Advances in recurrence and malignant transformation of sinonasal inverted papillomas - Sun, Qingjia (Oncol Lett, 2017)
Sinonasal inverted papilloma (SIP) is a benign tumor of the nasal cavity and sinus. SIP is characterized by aggressive malignant transformation and a high rate of recurrence. Inadequate removal of the tumor during surgery is one of the most significant contributors to SIP recurrence. A growing body of evidence suggests that molecular alteration in SIP, including human papilloma virus infections, single nucleotide polymorphisms of key genes, deregulation of signaling pathways and immunological changes, may lead to SIP occurrence and malignant transformation. However, the extent to which these molecular mechanisms contribute to SIP pathology and transformation remains unclear due to limited research. Further studies are warranted to elucidate the primary dependent factors that contribute to SIP etiology. The present article reviewed risk factors of progression and recurrence of SIP, including outdoor and industrial occupational exposure, smoking, septal deviation, SIP location, recurrent cases, stage of SIP-associated squamous cell carcinoma and choice of surgical method.